AI based intelligent transportation system for smart nations: A - Ong, Kerlyn Shi Yi (Nanyang Technological University, 2022)
As people become more affluent and can have car ownership, roads get congested with increasing vehicle population and accidents may occur, especially in a country like Singapore. Traffic congestion has thus become a common occurrence even with the current pandemic. To minimise and reduce all these from happening too often, many systems have been implemented to control traffic congestion, be it technological advancements or through monetary means.